2013
DOI: 10.1080/0092623x.2011.628439
|View full text |Cite
|
Sign up to set email alerts
|

Surviving a Gender-Variant Childhood: The Views of Transgender Adults on the Needs of Gender-Variant Children and Their Parents

Abstract: Adults with gender-variant childhoods have often lived traumatic lives because of the attitudes and limited understanding that people in their environment had of the concept of gender variance. This study explores the childhoods of transgender adults with the aim to understand their gender-related difficulties as children, in order to identify their needs and the needs of their parents at that time. The authors conducted a semi-structured survey with 110 transgender adults in order to explore their retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 21 publications
2
42
0
2
Order By: Relevance
“…A study by Riley, Clemson, Sithartan, and Diamond (2013) looking at adults in Australia with gender variant childhoods found that many of the participants had been ridiculed and attacked as children often resulting in low self-esteem and fear. Yet little is known about prevalence rates of self-harming in this group of young people.…”
Section: Discussionmentioning
confidence: 98%
“…A study by Riley, Clemson, Sithartan, and Diamond (2013) looking at adults in Australia with gender variant childhoods found that many of the participants had been ridiculed and attacked as children often resulting in low self-esteem and fear. Yet little is known about prevalence rates of self-harming in this group of young people.…”
Section: Discussionmentioning
confidence: 98%
“…Resilience theory emphasizes support within these environments, including family environments, as a key factor in the development of resilience among children facing stress (Sameroff, 2009). Quantitative data from LGBTQ youth suggest that acceptance in peer, family, and school social settings supports adjustment (Grossman, D’Augelli, & Frank, 2011; Ryan, Russell, Huebner, Diaz, & Sanchez, 2010); conversely, experiences of stigma have been linked to lower levels of psychological well-being among GV youth and young adults presenting for gender-related treatment (Baams, Beek, Hille, Zevenbergen, & Bos, 2013). These quantitative data are supported by qualitative data from transgender adults emphasizing experiences of rejection from parents, schools, and social contexts (Levitt & Ippolito, 2013, 2014).…”
Section: Studying Contextmentioning
confidence: 99%
“…Many parents need support in managing stigma and efficiently advocating on their children's behalf (Riley et al, 2011) as well as accessing information and specialized services or educating others (such as service providers) about their children's needs and experiences (Riley, Sitharthan, Clemson, & Diamond, 2013). Wren's (2002) interviews with parents of gender-variant teenagers revealed that how parents understood their children's transgenderism is iteratively linked to their capacity for acceptance.…”
mentioning
confidence: 98%